2016
DOI: 10.1053/j.ajkd.2015.07.031
|View full text |Cite|
|
Sign up to set email alerts
|

Low-Sodium Versus Standard-Sodium Peritoneal Dialysis Solution in Hypertensive Patients: A Randomized Controlled Trial

Abstract: The noninferiority of the low-sodium PD solution for total Kt/Vurea could not be proved; however, it showed beneficial clinical effects on sodium removal and BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 25 publications
0
31
0
4
Order By: Relevance
“…These outcomes were attributed to a reduction in thirst and fluid intake in the treatment group, potentially reducing fluid overload and urine excretion (similar to salt-restricted diet intervention), which led to a significant reduction in renal Kt/V in the treatment group. There was a trend towards improved blood pressure control in the low-sodium group although more patients developed hyponatraemia than the control group [81]. In light of the paucity of evidence to date and the presence of some safety signals, low-sodium PD solutions cannot be routinely recommended for clinical practice at this stage.…”
Section: Pd Solutions: Futurementioning
confidence: 95%
“…These outcomes were attributed to a reduction in thirst and fluid intake in the treatment group, potentially reducing fluid overload and urine excretion (similar to salt-restricted diet intervention), which led to a significant reduction in renal Kt/V in the treatment group. There was a trend towards improved blood pressure control in the low-sodium group although more patients developed hyponatraemia than the control group [81]. In light of the paucity of evidence to date and the presence of some safety signals, low-sodium PD solutions cannot be routinely recommended for clinical practice at this stage.…”
Section: Pd Solutions: Futurementioning
confidence: 95%
“…For haemodialysis patients, restricting sodium intake and increasing sodium removal by the use of lower dialysate sodium concentrations leads to an improvement in blood pressure control [19][20][21]. Similarly, both dietary sodium restriction and lower sodium dialysates been reported to lower blood pressure in peritoneal dialysis patients in the short term [13,22].…”
Section: Discussionmentioning
confidence: 99%
“…The glucose concentration can be increased in these solutions to maintain osmotic pressure and prevent decline in ultrafiltration (i.e., compensated low-sodium PD solutions). In a randomized controlled trial on 108 patients treated with CAPD, use of a modestly low-sodium solution (i.e., 125 mmol/L) in all dwells resulted in a marked increase in SR by 50 mmol/day [27]. The authors observed a trend towards decreased thirst in the low-sodium group.…”
Section: Potential Future Approachesmentioning
confidence: 99%